Ecotoxicological assessment of complex environmental matrices from the lower Paraná River basin - Peluso, Julieta; Pérez Coll, Cristina Silvia; Rojas, Dante Emanuel; Cristos, Diego Sebastian; Aronzon, Carolina Mariel (Elsevier, 2022)
Sediments of aquatic ecosystems constitute the fate of most atmospheric and terrestrial pollutants. Since aquatic organisms, such as amphibians, interact with sediments, the presence of pollutants may affect their survival, growth and reproduction. So, the aim of this study was to evaluate, the sediment and water quality of five sites from the lower basin of the Paraná River (Buenos Aires, Argentina) with different anthropic impacts: Morejón stream (S1), de la Cruz stream upstream (S2) and downstream (S3), Arrecifes river (S4), tributary stream of Arrecifes river (S5). Physicochemical parameters were measured in situ (water) and in laboratory (water and sediment samples). Also, a screening of metals and pesticides was performed. Chronic (504 h) lethal toxicity bioassays were performed exposing Rhinella arenarum larvae to sediment and water samples. Oxidative stress (catalase, superoxide dismutase, glutathione S transferase, reduced glutathione and lipid peroxidation) and genotoxicity (micronuclei test) biomarkers were analyzed at acute (96 h) exposure. According to the calculated water quality index, S1 and S3 showed excellent quality, S2 good quality and, S4 and S5 poor quality. Dissolved oxygen was low in all sites (2.26–5.63 mg/L) and S5 had the highest organic matter content. Copper levels exceeded the limit for the protection of aquatic life in S2 and S4; arsenic levels exceeded its limit in S4; and selenium levels exceeded its limit in S4 and S5. Pesticides were mainly detected in water samples. Sediment from S5 showed higher sulfide and organic matter concentrations. At 504 h, no significant mortality was observed in the control group while S5 caused the greatest mortality (80%), followed by S2 (66.67%), S1 (63.33%), S3 (46.67%) and S4 (43.4%). All samples caused oxidative stress and lipid peroxidation, and samples from S4 also caused genotoxicity. The analysis of sediment and water samples was a suitable approach to assess the effects of water bodies on a native amphibian species.